2006
DOI: 10.1002/bdm.546
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Bonus of rebate?: The impact of income framing on spending and saving

Abstract: Bonus of Rebate?: The Impact of Income Framing on Spending and Saving. By N. Epley, D. Mak and L. C. Idson (Journal of Behavioral Decision Making, Vol. 19, No. 3, pp. 213–227, 2006). DOI: 10.1002/bdm.519The above paper was published with an error in the title. The title should read: Bonus or Rebate?: The Impact of Income Framing on Spending and Saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This reflection has been referred to as 'loss aversion' (cf. Kahneman & Tversky, 1979) and has been reported in consumer, health, and economic decision-making processes (Diacon & Hasseldine, 2007;Epley, Mak, Idson, 2006;McNeil, Pauker, Sox, & Tversky, 1982;Sanford, Fay, Stewart, & Moxey, 2002). Further evidence has suggested that framing effects and, by extension, loss aversion, are part of an affective type 1 heuristic process (Cassotti et al, 2012;Kahneman & Frederick, 2007).…”
Section: Dual-process Theory Financial Literacy and Numeracymentioning
confidence: 94%
“…This reflection has been referred to as 'loss aversion' (cf. Kahneman & Tversky, 1979) and has been reported in consumer, health, and economic decision-making processes (Diacon & Hasseldine, 2007;Epley, Mak, Idson, 2006;McNeil, Pauker, Sox, & Tversky, 1982;Sanford, Fay, Stewart, & Moxey, 2002). Further evidence has suggested that framing effects and, by extension, loss aversion, are part of an affective type 1 heuristic process (Cassotti et al, 2012;Kahneman & Frederick, 2007).…”
Section: Dual-process Theory Financial Literacy and Numeracymentioning
confidence: 94%
“…This accompanies the assumption that people tend to maintain stable preferences over time and are not affected by the framing of the income they receive. 2 However, evidence shows some deviations from these predictions (Shapiro and Slemrod, 2003;Epley et al, 2006;Milkman and Beshears, 2009), which are difficult to explain under this theoretical framework (e.g. tax rebates failing to boost the economy and coupons leading to unusual consumption patterns).…”
Section: From Classical Theory…mentioning
confidence: 99%
“…Although there are many reasons why people may choose to spend or save, Epley et al (2006) and Epley and Gneezy (2007) suggest that the way people label these rebates may have a significant impact. Windfalls are more likely to be saved when labeled as a refund, and they are more likely to be spent when labeled as a bonus.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation